Pelatihan dan Pengenalan Elektronika Serta Dasar Koding Menggunakan Tinkercad di MAN Insan Cendekia Pekalongan - Joni Apriyanto; Prihastanto (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2025)
The development of Information and Communication Technology in the last few decades has experienced very rapid progress and has had a broad impact on various aspects of life, ranging from social, economic, health, to education. In the context of electrical engineering and coding education, various simulation-based digital learning platforms have begun to be widely used to replace or complement conventional practices. One such platform is Tinkercad, a web-based application that allows users to create virtual electronic circuit simulations and program microcontrollers such as Arduino. This platform is very suitable for use in the process of learning the basics of electronics and programming (coding) because the interface is simple and easy to understand for beginners. For this reason, the Community Service Activity of Indraprasta PGRI University was carried out by holding an introduction to coding training for electrical applications with Tinkercad for students of MAN Insan Cendekia Pekalongan and was carried out online. The purpose of this training is to introduce basic electricity and basic programming and its application in the world of electricity. The training method is in the form of lectures and practice in making simple electrical circuits and ends with making a traffic light project using Arduino programmed through the Tinkercad platform. The training participants were invited to understand the basic electrical concepts, get to know electrical components, understand the basic concepts of programming and compile circuits and program codes in stages. The results of the training showed an increase in students' understanding of the basic concepts of electricity, microcontrollers and programming. This training is expected to be the first step in encouraging digital literacy and technological skills for MAN IC Pekalongan students in the era of the industrial revolution 4.0.